Analisis Produksi dan Keuntungan Komoditi Jagung (Zea mays L) di Desa Kemiri Timur Kecamatan Subah Kabupaten Batang Provinsi Jawa Tengah - Vita Magdalena; Nugrahini Susantinah Wisnujati; Ristani Widya Inti (Jurnal Ilmiah Sosio Agribis, 2022)
Corn is the second most important food commodity after rice. One of the mainstay commodities in the agricultural sector is corn, because corn is one of the staple foods in Indonesia which has an important position after rice. The objectives of this study are 1. to analyze the factors that influence corn production in Kemiri Timur Village, District, 2. To analyze the income of corn farmers in Kemiri Village, Subah District. The research method used is the Random Sampling method. Respondents in this study were 30 owner farmers. The data collection method used primary data and secondary data. The data analysis method used multiple linear regression analysis. Based on the results of multiple linear regression, the maize production mode in Subah District is as follows: Y = -2.237 – 0.751X2 + (-0,220)X3 + 0.194X4 + (-0.023)X5 + e. Based on the F-statistic of 133,218 with a significance of 0.000%, it means that simultaneously all production activities carried out including corn fields, labor, seeds and fertilizers have a significant effect on corn production in Subah District, Batang Regency. Partially, production activities that have a significant effect on income are land area and labor.Keywords : Corn Plants, Multiple Linear Regression Analysis, Profit Analysis